Adaptive network-aided session support in context-aware converged mobile networks. (9th July 2012) - Antoniou, Josephina; Christophorou, Christophoros; Simoes, Jose; Pitsillides, Andreas
The increase of networking complexity requires the design of new performance optimisation schemes for delivering sessions to users under different conditions. This paper addresses context-aware, adaptive multiparty sessions in a heterogeneous network environment. The effective usage of context information can lead to context-aware content casting, especially context-aware, adaptive multicasting. Efficient multiparty delivery depends upon grouping (creation of a set of users to receive a given session), which must be done based on several parameters; both at session and at network level. Therefore, the key functionality of an enhanced session management is to motivate creation of user subgroups, subsets of a content group based on network, user and environment context. Their characteristics in the form of content descriptions are communicated to the media delivery to obtain the appropriate content for each session. This paper presents in detail the initiation of an adaptive, context-aware multicast session.